2021
DOI: 10.1111/ggi.14153
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of mortality and in‐hospital complications in hip fracture surgery: Retrospective cohort research using a nationwide inpatient database

Abstract: Among older patients undergoing hip fracture surgery, previous studies have shown a seasonal variation of in-hospital surgical complications. However, little is known about seasonal effects on mortality and systemic complications after hip fracture surgery. In the present study, we evaluated whether mortality and in-hospital systemic complications are influenced by seasonal differences.Methods: We enrolled patients from a nationwide database who underwent hip fracture surgery between 2010 and 2018. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Several studies have demonstrated characteristic seasonality in hip fractures [ 10 , 15 17 ]. The present study clearly demonstrated an increase in the number of patients with hip fracture in winter, and a decrease in summer, consistent with the findings of Hagino et al [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated characteristic seasonality in hip fractures [ 10 , 15 17 ]. The present study clearly demonstrated an increase in the number of patients with hip fracture in winter, and a decrease in summer, consistent with the findings of Hagino et al [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of 0.43% in this study was extraordinarily low compared to previous epidemiological research. Stenqvist et al [ 24 ] and Ogawa et al [ 17 ] reported overall in-hospital mortality rates of 6.3% and 1.2%, respectively. Although detailed reasons for our result remain unclear, this inconsistency might be partially attributable to the relatively short observation period in our study, compared to the mean lengths of hospitalization of 24.9 days [ 24 ] and 35.96 days [ 17 ], respectively, in those previous investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and increased bone fragility in older patients due to seasonal variation in parathyroid hormone and vitamin D levels [1,11,12]. Various studies have also demonstrated a higher mortality rate associated with hip fractures in geriatric patients during the winter months [2,4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature attributes some of the increased mortality to a worsening of pre-existing pulmonary and cardiovascular conditions and higher rates of pulmonary infections in geriatric patients during winter [13,15].…”
Section: Introductionmentioning
confidence: 99%